THE TRANSLATION OF CULTURE-SPECIFIC ITEMS IN NGERI-NGERI SEDAP MOVIE - Adawiyah, Siti Lutfiah Rabiyatul; Andriyanti, Erna; Ashadi, Ashadi; Anwar, Saiful (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2023)
Translating culture-specific items (CSI) is difficult because the cultural items of the source language do not necessarily have the exact equivalent in the target language. This study aimed to describe the types of CSI in Ngeri-Ngeri Sedap movie based on Newmark’s (1988) categorization, Molina and Albir’s (2002) translation technique, and the translation norms. It employed descriptive qualitative research, and the data were collected using note-taking technique. The study results found 60 cultural items based on Newmark’s parameter types. The most frequently employed CSI type is socio-culture, with 29 data instances. Additionally, the category of the organization was observed in 20 instances, material culture was found in 8 instances, gesture and habit were present in 2 instances, and ecology was represented in 1 instance of data. 10 out of 18 translation techniques were used, but the most widely used translation technique was the literal translation, with 16 instances. Meanwhile, three dominant techniques were literal, adaptation, and generalization, which became the translation norms of CSI. The literal translation technique shows the closeness of SL (Source Language) and TL (Target Language) so that several concepts already have equivalents following the meaning of the SL.